Peningkatan Kualitas Mubaligh Hijrah Masjid di Yogyakarta melalui Literasi Hadis Nabi - Waharjani; Mohammad Jailani (Warta LPM, 2024)
The problems that the takmir of the Daliatul Iman mosque feel are (1) that the Friday preachers of Dalilatul Iman are mostly from outside members of the congregation and mosque takmir administrators; (2) many of them are elderly; (3) material concerning the issue of the hadith of the Prophet Muhammad. What was conveyed in the Friday sermon was not in accordance with the rules for taking reference material sources properly. Responding to the three problems raised by the takmir administrators of the Dalilatul Iman mosque, the proposing team offered three structured and systematic solutions. Organizing Friday khatib training for prospective khatib and novice khatib from takmir administrators and mosque congregation members who are recommended by takmir administrators and from surrounding mosque takmir administrators who register and meet the requirements proposed by management of partner mosques upon consideration. Input from the proposing team. This solution is in accordance with the competence of the proposing team, as a trainer the chairman of the Dalilatul Iman mosque takmir agrees to the solution offered by the proposing team, even other mosque administrators will also contribute to this activity. Implementation methods applied are socialization, training, mentoring, evaluation and monitoring. Counseling twice was carried out to 9 heads of Ta'mir mosques in Annual with material on the importance of the role of the preacher in the prosperity of the mosque. Friday sermon improvement training, especially in conveying the source of the hadith of the Prophet Muhammad. The training was given to 20 novice Friday sermon candidates with materials: Friday sermon procedures, Friday sermon practice simulations, Friday sermon preparation practice, and direct practice of Friday sermons at partner mosques. The training was completed and resulted in young Friday preachers who were ready to carry out their duties, and now they are on active duty.